Strategi Kepala Sekolah Dalam Kebijakan Pembelajaran Pada Masa Pandemi Covid-19 di Sekolah Dasar - Ahmad Nashihin Agus Saputro; Abu Darim (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2022)
The research objectives are to determine: 1). Planning, 2) Organizing, 3) Implementation and 4) Supervising school principals in learning policies during the Covid-19 pandemic. This type of research is qualitative with a case study approach. Collecting data through observation, interviews, and documentation. The validity of the data employing triangulation. The results showed that the principal's strategy in learning policies during the Covid-19 pandemic at Maarif Jogosari Pandaan Elementary School, Pasuruan Regency, went well with seven policies, namely: 1) Implementing online learning 2) Establishing a school Covid-19 Task Force 3) Using an emergency curriculum 4) Determination of Attendance Schedule for Educators and Education Personnel with a picket schedule 5) Eliminating extracurricular activities 6) Implementing limited face-to-face learning activities 7) Reducing education costs.